A policy framework for e-money: A report on Bank of Canada Research - Mohammad Davoodalhosseini; Francisco Rivadeneyra (Bank of Canada, 2018)
We present a policy framework for electronic money and payments. The framework poses a set of positive questions related to the areas of responsibility of central banks: payments systems, monetary policy and financial stability. The questions are posed to four broad forms of e-money: privately or publicly issued, and with centralized or decentralized verification of transactions. This framework is intended to help evaluate the trade-offs that central banks face in the decision to issue new forms of e-money.
Keywords: E41; E51; E52; E58; 330; Digital Currencies; Monetary Policy; Payment clearing and settlement systems